2009
DOI: 10.2166/wst.2009.738
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen sulphide removal in the anaerobic digestion of sludge by micro-aerobic processes: pilot plant experience

Abstract: H(2)S removal from biogas produced in anaerobic digestion of sludge through the introduction of oxygen under micro-aerobic conditions is studied. Research was carried out in two pilot plant reactors (working volume, 200 L each) treating sludge from WWTP with HRT of 20 days. Mixing was provided via sludge or biogas recirculation. Introduction of very low oxygen flow (0.013-0.024 L/L(reactor) d) successfully removed H(2)S content in biogas with an efficiency above 99%. Reactor performance during micro-aerobic op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 8 publications
(8 reference statements)
1
33
0
2
Order By: Relevance
“…This may improve the economy of biogas generation plants enhancing the dissemination of such sustainable solutions. Partial aeration assisted anaerobic digestion has been recognized as a possible way to enhance AD performance [27][28][29][30].…”
Section: Anaerobic Digestionmentioning
confidence: 99%
See 3 more Smart Citations
“…This may improve the economy of biogas generation plants enhancing the dissemination of such sustainable solutions. Partial aeration assisted anaerobic digestion has been recognized as a possible way to enhance AD performance [27][28][29][30].…”
Section: Anaerobic Digestionmentioning
confidence: 99%
“…Several studies [29,80,86,98] have demonstrated that limited aeration can be used to oxidize the sulfides generated in anaerobic digesters operating on S containing wastes. In anaerobic digestion, S compounds are reduced to HS -and H 2 S by the biological activity of anaerobic sulfate reducing bacteria (SRB) [99].…”
Section: Sulfide Oxidationmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent research suggests, however, that a limited availability of free oxygen can be beneficial in a number of ways to make AD more efficient and flexible as a waste treatment and energy generation scheme (Johansen and Bakke, 2006;Polanco et al, 2009;Botheju et al, 2010a,b). Studying effects of limited oxygen supply in operation of AD is relevant also since maintaining meticulously anaerobic systems is often not easy.…”
Section: Introductionmentioning
confidence: 99%